2002
DOI: 10.1583/1545-1550(2002)009<0165:ssgrot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Stent-Graft Repair of Thoracic and Infrarenal Abdominal Aortic Aneurysms

Abstract: Simultaneous endovascular treatment of thoracic and infrarenal abdominal aortic aneurysms may represent a viable alternative for therapy in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Cuypers et al 9 concluded that hemodynamic changes during stent-graft repair were not as severe as those that occurred during open surgery, and resulted in less myocardial stress. We also think that stent-graft repair is Wolf et al 10 and Meguid et al 11 described performing simultaneous stent-graft repair of concomitant TAA and AAA. We considered open and endovascular repair options for our patient, but the dual aneurysms and recent episode of myocardial infarction placed her at too high a risk for an open repair.…”
Section: Discussionmentioning
confidence: 92%
“…Cuypers et al 9 concluded that hemodynamic changes during stent-graft repair were not as severe as those that occurred during open surgery, and resulted in less myocardial stress. We also think that stent-graft repair is Wolf et al 10 and Meguid et al 11 described performing simultaneous stent-graft repair of concomitant TAA and AAA. We considered open and endovascular repair options for our patient, but the dual aneurysms and recent episode of myocardial infarction placed her at too high a risk for an open repair.…”
Section: Discussionmentioning
confidence: 92%
“…The estimated incidence of simultaneous thoracic and abdominal aortic disease is approximately 10-20% of the patients [1][2][3][4][5]. There is a very little data available for combined thoracic and abdominal aneurysm repair; historically simultaneous thoracic and abdominal aortic disease repair showed to be a challenging surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal aortic disease included atherosclerotic infrarenal (nZ3) and juxtarenal (nZ1) aortic aneurysms. Mean abdominal aortic aneurysm (AAA) diameter was 67G13 mm (range, [5][6][7][8]. Mean thoracic aortic lumen measured 33.5 mm (range 30-38 mm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,20,27,35 These could also be used to better diagnose the disease progression, assess the feasibility of an EVAR procedure, and design better stent-grafts. Although 2D deformable models (in image reconstruction) give a good approximation to the true shape, the resulting geometry may not be smooth (owing to a lack of proper interpolation of intensity between successive image slices) when lofted using CAD.…”
Section: Introductionmentioning
confidence: 99%